Analisis Yuridis Penerapan Keadilan Restoratif pada Tindak Pidana Penipuan dan Penggelapan Berdasarkan Undang-Undang Nomor 1 Tahun 2023 - Puguh Triwibowo (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code and Law Number 20 of 2025 concerning the Criminal Procedure Code marks an integrated shift in Indonesian criminal law from a predominantly retributive orientation toward corrective, rehabilitative, and restorative justice. Fraud and embezzlement are offenses against property that cause directly measurable losses and frequently intersect with civil disputes. This study analyzes the legal characteristics of fraud and embezzlement under the National Criminal Code and examines the requirements, stages, and legal consequences of restorative settlement under the National Criminal Procedure Code. The research employs normative legal research using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials that are analyzed qualitatively through grammatical, systematic, and teleological interpretation. The study finds that fraud under Article 492 and embezzlement under Article 486, each carrying a maximum imprisonment of four years, may in principle enter a restorative mechanism because their penalties fall within the statutory threshold. Nevertheless, eligibility must be tested through the voluntariness of the parties, full restoration of the victim’s loss, the offender’s record, the public impact of the offense, and the absence of prohibited categories. The new procedural framework strengthens legal certainty by requiring written agreements, fulfillment of restoration, termination of proceedings, and court confirmation. Effective implementation therefore depends on consistent inter-institutional standards, transparent supervision, and protection against coercion or transactional impunity.